2022
DOI: 10.1088/1674-1137/ac5f9c
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic form factors of neutron and neutral hyperons in the oscillating point of view *

Abstract: Based on the recently precise measurements of the electron-positron annihilation reactions into a neutron and anti-neutron pair by BESIII collaboration, the effective form factor of neutron was determined in the time like region, and it was found that the effective form factor of neutron is smaller than the ones of proton. The effective form factors of neutron shows a periodic behaviour, similar to the case of proton. Here, a compared analysis for $\Lambda$, $\Sigma^0$ and $\Xi^0$ is performed. Fits of the ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The relative phase of the Λ EMFFs was extracted by fitting the angular distributions [21]. Many theoretical activities [30][31][32][33][34][35] arose after this measurement. In Ref.…”
mentioning
confidence: 99%
“…The relative phase of the Λ EMFFs was extracted by fitting the angular distributions [21]. Many theoretical activities [30][31][32][33][34][35] arose after this measurement. In Ref.…”
mentioning
confidence: 99%
“…= 0.6. The fitted result for the parameter 𝛾 is 0.147 ± 0.017 GeV −2 , which is smaller than the typical values for the light baryons nucleon, [47,48] 𝛬, [14,47] 𝛴, [12,47] and 𝛯. [12] Table 2 Fig.…”
Section: λ−mentioning
confidence: 65%
“…[21], does not exhibit oscillatory behavior, in contrast to the findings in the nucleon case. [47,[49][50][51][52][53][54] This may be attributed to the limited energy range considered for the 𝑒 + 𝑒 − → 𝛬 + 𝑐 Λ− 𝑐 reaction. The range from the reaction threshold to 4.95 GeV is only about 350 MeV.…”
Section: λ−mentioning
confidence: 99%
“…In the vector meson dominance model for studying the electromagnetic form factors of baryons, there is a phenomenological intrinsic form factor g(q 2 ). From these studies of the nucleon and hyperon EMFFs [17][18][19][20][21][22][23][24][25][26][27][28][29], it is found that a better choice of g(q 2 ) is the dipole form…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, the simple dipole form paremetrization is very useful for the discussion of different baryons. For example, the dipole form of g(q 2 ) can well describe the effective form factors of Λ [20,21], Σ [32], and Ξ [27]. While for the nucleon, a good general review is given in Refs.…”
Section: Introductionmentioning
confidence: 99%